Supplier preferences in Turkish grocery sector - Ünlü, Mehmet Ali (My University, 2001)
Türkiye'de modern gıda perakendeciliği kavramı gelişme dönemini yaşamaktadır. Yoğun rekabet ve enflasyon istikrarsız ekonomik yapıyla birlikte dağıtım kanalları karmaşık bir hal almıştır. Bu karmaşıklıktan en çok etkilenen özellikle bakkaliye sektörü olmuştur. Yaşanan yoğun fiyat rekabeti, spot piyasanın ortaya açıkması, ve bakkalların hypermarketleri zaman zaman tedarikçi olarak kullanmaları, üreticilere bağlı olarak çalışan ve bakkallara hizmet veren distributörleri zor durumda bırakmıştır. Çünkü bakkallara yönelik tedarik kanalları artmıştır. Bu araştırmanın amacı bakkaliye sektöründeki dağıtım sistemini, bakkalların tercihlerini ve bu tercihleri etkileyen faktörlerle birlikte ortaya koymaktır. Araştırma sonucunda, yaşanan yoğun rekabete rağmen üreticilerin en önemli tedarikçi oldukları görülmüştür. Markanın kalitesinden ve düzenli dağıtımından sorumlu ve aynı zamanda üreticiyi temsil eden firma yetkilisinin tercih edilmesinin en önemli sebebi düzenli servis ve iade garantisidir. Ancak ürün markasının sahibi olan üretcilerin fiyat bazında diğer tedarikçilerle rekabet edemedikleri görülmüştür. Üreticilerin distribütörlerine satış kotalarına ulaşmak için yaptığı talep fazlası satışların dağıtım kanallarında ortaya çıkardığı karmaşıklık, toptancıları ve spot piyasayı üreticilere karşı alternatif tedarikçi olarak güçlendirmektedir. Bu bağlamda dağıtıcı firmalar gelecekte, stok miktarlarını azaltmayı, depolama kalitesini yükseltmeyi, efektif sipariş almayı, stoksuzluk riskini azaltmayı ve pazarlama faaliyetlerinden çok direk satış ve dağıtım yapmayı hedefleyeceklerdir.

Concept of modern food retailing, is at the developing stage in Turkey. The high levels of competition and inflation, together with instable economic structure, causes chaos in distribution networks. This affects the grocery sector the most. The competition in terms of prices, the appearance of the spot market, and the groceries' use of hypermarkets as suppliers has left the distributors working for the producers in a difficult situation, as the distribution channels for the groceries have increased. The aim of this research is to present distribution system in grocery sector with exploring the supplier preferences and finding out the variables that influence the preferences of groceries in Turkey. It was found that, although there is a deep competition in this sector, producers are the most important suppliers in grocery sector. The most important reason is regular service and buy back guarantee, meaning the grocery owner is dealing with the representative of the official brand name who is directly responsible for the quality of the products and smooth flow of supply. Although producers are the owner of the brands, they cannot compete with the other suppliers in terms of price. The irregularity of supply and distribution arising from excessive sales by the producers to meet quotas is strengthening the wholesalers and the spot market as an alternative supplier for the groceries. And also through various techniques, hypermarkets are able to get below actual producer prices and become cheapest supplier for certain products in certain periods, both for the consumers as well as the retailers. In this respect the near future targets of the distributors are decreasing the stock quantities, increasing the quality of storing, taking effective orders, decreasing the risks of non stock and making direct sales and distribution instead of marketing activities.
Keywords: Gıda Sanayi; İç ticaret; Perakende Ticaret; Ticaret